PENGARUH INTELLECTUAL CAPITAL TERHADAP NILAI PERUSAHAAN DENGAN KINERJA KEUANGAN SEBAGAI VARIABEL MEDIATOR PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - LITA ASTARI; ISNURHADI . (Program Studi Magister Manajemen FE Unsri, 2015)
The purpose of this study is to investigate whether intellectual capital affect the firm value. Furthermore, firm performance as mediating variable is also investigated. A component of intellectual capital is used as independent variables. They consists of Human Capital Efficiency (HCE), Capital Employed Efficiency (CEE), and Structural Capital Efficiency (SCE). Onthe other hand, Price to Book Value (PBV) is used as dependent variable and Return on Equity (ROE) as mediating variable. The population is all companies listed in Indonesia Stock Exchange (IDX) for the year 2013. Purposive sampling is used to select sample which is totally 109 observation. Path analysis is employed to analyze data. The result shows that HCE has positive impact on ROE but CEE and SCE do not. HCE has positive effect on PBV but CEE and SCE do not. ROE mediates the relationship CEE on PBV but the ROE does not mediate the relationship between HCE and SCE on PBV. Finally, ROE has positive effect on PBV